Perancangan Rusunawa dengan Pendekatan Arsitektur Berkelanjutan di Rawa Buaya, Cengkareng, Jakarta Barat - Ulima, Yasmin Alodia (Jurnal Arsitektur Wastu Padma, 2024)
Rapid urbanization in West Jakarta has increased the need for sustainable housing, especially in Rawa Buaya, Cengkareng. This research designed Rusunawa with a sustainable architectural approach that prioritizes energy efficiency, waste management, and environmentally friendly materials. The methods used include case studies and sustainable design analysis through field observations, expert interviews, and literature reviews. The study's results offer the concept of Rusunawa, which meets decent housing standards while supporting environmental conservation. This finding is expected to guide the design of sustainable flats and can be applied more widely in other urban areas.